MATERNAL ANXIETY AND DEPRESSION IN WOMEN WITH PREGNANCY LOSSES DURING THE FIRST TRIMESTER - ABID NISAR KHAN, ASMA RIAZ², SAFIA FAZAL, FAIZA NAWAZ KHAN, MASHAL IFTIKHAR, HABIB ULLAH (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Recurrent pregnancy loss (RPL), defined as two or more consecutive miscarriages before 24 weeks of gestation, significantly impacts women’s physical and psychological well-being. Anxiety and depression are commonly reported in women experiencing RPL, but their role in the recurrence of pregnancy loss remains inadequately explored. This study aims to assess the relationship between maternal anxiety, depression, and the risk of recurrent pregnancy loss, examining both the psychological distress associated with RPL and its potential contribution to the recurrence of pregnancy loss. The primary objective was to investigate the association between maternal anxiety, depression, and recurrent pregnancy loss. A secondary objective was to explore whether psychological distress contributes to the risk of subsequent pregnancy loss. Methods: A prospective observational cohort study was conducted at Ayub Teaching Hospital, Abbottabad, Pakistan, enrolling 50 women with a history of recurrent pregnancy loss. Anxiety, depression, and stress were assessed using the Depression, Anxiety, and Stress Scale-21 (DASS-21). Sociodemographic data and pregnancy outcomes were collected. Statistical analyses, including logistic regression, were employed to evaluate the relationship between psychological distress and pregnancy outcomes. The study found significant levels of psychological distress, with one-third of participants reporting clinically relevant anxiety and depression symptoms. The logistic regression analysis revealed a significant association between higher anxiety and depression levels and increased risk of recurrent pregnancy loss (p < 0.05). Women with both anxiety and depression had an adjusted odds ratio (OR) of 2.788 (95% CI: 1.511–5.144), indicating a synergistic effect of these psychological conditions on the recurrence of pregnancy loss. Conclusions: This study provides compelling evidence that maternal anxiety and depression play a significant role in the recurrence of pregnancy loss. Elevated psychological distress was found to be both a cause and consequence of recurrent pregnancy loss, contributing to a cyclical pattern of emotional and reproductive challenges. Addressing mental health in women with RPL could improve pregnancy outcomes and reduce the burden of recurrent miscarriage. Further research is needed to explore the underlying biological mechanisms linking psychological distress with RPL and to evaluate the effectiveness of psychological interventions in improving reproductive health outcomes.